Investigation of Structural and Thermal Evolution in Novel Layered Perovskite NdSrMn2O5+δ via Neutron Powder Diffraction and Thermogravimetric Analysis - Shammya Afroze; Duygu Yilmaz; Md Sumon Reza; Paul F. Henry; Quentin Cheok; Juliana H Zaini; Abul K. Azad; Alibek Issakhov; Milad Sadeghzadeh (International Journal of Chemical Engineering)
Neutron diffraction is one of the best methods for structural analysis of a complex, layered perovskite material with low symmetry by accurately detecting the oxygen positions through octahedral tilting. In this research, the crystal structure of NdSrMn2O5+δ was identified through X-ray diffraction (XRD) and neutron powder diffraction (NPD) at room temperature (RT), which indicated the formation of a layered structure in orthorhombic symmetry in the Pmmm (no. 47) space group. Rietveld refinement of the neutron diffraction data has confirmed the orthorhombic symmetry with unit cell parameters (a = 3.8367 (1) Å, b = 3.8643 (2) Å, and c = 7.7126 (1) Å), atomic positions, and oxygen occupancy. Thermogravimetric analysis revealed the total weight loss of about 0.10% for 20–950°C temperature, which occurred mainly to create oxygen vacancies at high temperatures. Rietveld analyses concurred with the XRD and neutron data allowing correlation of occupancy factors of the oxygen sites.